2021
DOI: 10.1096/fj.202002323r
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of inactivation and the roles of Elovl3 /ELOVL3 in maintaining ocular homeostasis

Abstract: The holocrine Meibomian glands (MG) reside within the tarsal plates (TP) of the eyelids of humans and most of other mammals and secrete an oily substance called meibum. 1 The chemical analyses of meibum revealed that it is composed predominantly of lipids with up to 20% of nonlipid inclusions. 2 Meibum lipids are believed to form the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In conclusion, inactivation of Soat1 confirmed its previously predicted critical role in meibogenesis [7,11,12,21,23] and led to an almost complete elimination of MG-derived CE and Chl-OAHFA ( Figure 9). This change in meibum caused dramatic shifts in the ocular phenotype of Soat1-ablated mice that resembled many features characteristic of human MGD.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In conclusion, inactivation of Soat1 confirmed its previously predicted critical role in meibogenesis [7,11,12,21,23] and led to an almost complete elimination of MG-derived CE and Chl-OAHFA ( Figure 9). This change in meibum caused dramatic shifts in the ocular phenotype of Soat1-ablated mice that resembled many features characteristic of human MGD.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, the makeup of CE in meibum demonstrated only subtle inter-donor variations in humans [12] and mice [21]. Recently, we reported that MG of humans highly expressed key genes of Chl biosynthesis, such as ACAT1/ACAT2, DHCR7, DHCR24, FDFT1, HMGCR, HMGCS1/HMGCS2, LSS, MSMO1, SQLE, and others, and so did MG of mice [7,11,12,23]. Genes that encode enzymes of CE biosynthesis via Chl esterification with FA-SOAT1/Soat1, SOAT2/Soat2, and LCAT/Lcat-were also identified.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations